Chronic Lymphocytic Thyroiditis and Aggressiveness of Pediatric Differentiated Thyroid Cancer. (23rd October 2021) - Yeker, Richard M.; Shaffer, Amber D.; Viswanathan, Pushpa; Witchel, Selma F.; Mollen, Kevin; Yip, Linwah; Monaco, Sara E.; Duvvuri, Umamaheswar; Simons, Jeffrey P.
Abstract : Objectives/Hypothesis: Hashimoto's Thyroiditis (HT) is a common cause of hypothyroidism. Among adults with differentiated thyroid cancer (DTC), HT appears to be associated with less severe disease burden. In the absence of information regarding HT and disease burden among children with DTC, we assessed the relationship between pediatric DTC severity and HT. Study Design: Retrospective cohort. Methods: Charts from 90 pediatric patients who underwent surgical removal of DTC from 2002 to 2017 at tertiary‐care children's hospital were reviewed. Demographic, clinical, surgical, pathology, and outcome details were compared between patients with and without HT. Consistency among diagnostic modalities of HT was also evaluated. Results: Median age at presentation was 16.0 years (range 4.2–18.9 years). Twenty‐two patients were male (24%). Forty‐five patients (50%) had HT based on presence of thyroid autoantibodies and/or surgical pathology findings and 45 patients did not have HT. Patients with HT had increased odds of microcalcifications (odds ratio [OR]: 3.01, P = .031) and decreased odds of palpable nodules (OR: 0.212, P = .024) and T2 lesions (vs. T1) (OR: 0.261, P = .015) compared with non‐HT. No significant differences in demographics and the incidence of multifocality, extrathyroidal extension, lymphovascular invasion, lymph node or pulmonary metastases, disease recurrence, or radioactive iodine treatment were found between the two groups. Thyroglobulin/thyroid peroxidase autoantibodies and surgical pathology indicative of HT were concordant in 82.4% ( κ = 0.635, P < .001). Conclusion: HT was present in 50% of children with DTC. Patients with DTC and HT presented with smaller tumors compared to non‐HT patients. No significant differences in other markers of disease aggressiveness were found between the two groups. Level of Evidence: 3 Laryngoscope, 132:1668–1674, 2022